2023
DOI: 10.1111/cas.15779
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐324‐3p inhibits osteosarcoma progression by suppressing PGAM1‐mediated aerobic glycolysis

Abstract: Osteosarcoma (OS) is the most common primary malignant neoplasm of the bone.Recent studies have indicated that the inhibitory effects of microRNA (miR)-324-3p could affect the development of numerous cancers. However, its biological roles and underlying mechanisms in OS progression remain unexplored. In this study, miR-324-3p expression was markedly reduced in OS cell lines and tissues. Functionally, miR-324-3p overexpression suppressed OS progression and was involved in the Warburg effect. Mechanistically, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…We found that PGAM1 expression was significantly higher in the majority of solid tumor tissues than in normal tissues. This result is highly consistent with the report of Hitosugi et al [41], indicating that the expression of PGAM1 in tumors is universal and specific. To verify whether the expression of PGAM1 mRNA was consistent with the changes in protein levels, we further analyzed the expression and prognosis of PGAM1 protein in tumors using the HPA database and found that PGAM1 was highly expressed in 9 types of tumors and associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that PGAM1 expression was significantly higher in the majority of solid tumor tissues than in normal tissues. This result is highly consistent with the report of Hitosugi et al [41], indicating that the expression of PGAM1 in tumors is universal and specific. To verify whether the expression of PGAM1 mRNA was consistent with the changes in protein levels, we further analyzed the expression and prognosis of PGAM1 protein in tumors using the HPA database and found that PGAM1 was highly expressed in 9 types of tumors and associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…PGAM1 is a key enzyme involved in glycolysis, and its expression level and functional regulation in a variety of tumors have received extensive attention [41,42]. In this study, we discussed the expression and function of PGAM1 in tumors and its possible regulatory mechanisms from multiple perspectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that PGAM1 plays a role in modulating the immune response and influencing immune cell function. It has been found to regulate the metabolic programming of immune cells, particularly T cells and macrophages, thereby impacting their effector functions and immune responses [ 47 ].…”
Section: Discussionmentioning
confidence: 99%